PENGEMBANGAN PEMBELAJARAN PAI MODEL ADDIE DI SMP INSAN CENDEKIA MENDIRI BOARDING SCHOOL, SIDOARJO - Muhammad Khairul Basyar (Universitas Muhammadiyah Prof Dr Hamka, 2020)
Education is the process of changing one's behavior through teaching and training so that they become more mature. The lack of application of PAI learning values ​​by students of SMP Insan Cendekia Mandiri Boarding School (ICMBS) Sidoarjo, has made the PAI teachers of SMP ICMBS innovate by developing integrated PAI learning. This is supported by the condition of school which based on the Boarding School. The purpose of this study is to describe how the development of ADDIE PAI learning model conducted by PAI SMP ICMBS teachers. The method used in this research is research and development methods. The results shows that the design of learning in the classroom is with the ADDIE model and with the concept of Building Learning Power (BLP). In addition, Teacher-centered methods sometimes also exist in schools. The development of PAI learning undertaken by SMP ICMBS teachers makes students better at implementing PAI learning values, beside the integrated PAI learning curriculum, as well as an excellent design system.